Biosecurity Practices Applied in Aquacultural Farms in Northern Senegal,West Africa - Faye, Robane; Diouf, Nicolas Djighnoum; Amadou LY, Mouhamadou; Ayih-Akakpo, Justin Ayayi (European Scientific Journal, ESJ, 2020)
This study was conducted in northern Senegal, covering the regions of Saint-Louis, Louga and Matam, from June 2016 to December 2016. Surveys were carried out at all farms in this area where fish, shrimp, and molluscs farming or grow-out activities are conducted. The sampling method used is the survey determined by respondents which is a variation of snowball sampling. This method allowed us to administer a questionnaire to the fiftynine farms in activity in northern Senegal. The overall objective of this paper is to contribute to the improvement of knowledge on aquaculture biosecurity in the study areas through the application of biosecurity measures. This study highlighted the interconnections between the different farms, identified biosecurity measures for infrastructure, livestock and food, and assessed the different biosecurity measures applied to staff. The results revealed that biosecurity measures are poorly implemented. 74.6% of the people surveyed are also unaware of the mechanisms by which aquatic animal diseases appear and spread out, while 86.4% of them have no knowledge of biosecurity in aquaculture. Our recommendations focus on the need to encourage aquaculture professionals to apply biosecurity measures at all production stages. There is also the need for training or capacity building for aquaculture farmers on biosecurity measures.